Pengaruh Penggunaan E-Learning Terhadap Motivasi Belajar Matematika Di SMP Negeri Kota Makassar - Nikodemus Nikodemus; Fathimah Az.zahra Nasiruddin; Jainuddin Jainuddin (Universitas Negeri Makassar, 2022)
This research was conducted to know the effect of e-learning on the mathematics learning motivation of eighth-grade students of SMP Negeri 35 Makassar. This research is quantitative design. The sample of this research is the students of class VIII- Seven which consists of 33 students. The research method used is quantitative. This type of research is experimental research. Data collection techniques used in this study were observation sheets and questionnaires.The results show that the use of e-learning affected students' learning motivation. The validity test process conducted it with the value of t- table 0.349, and the reliability test of learning motivation is 0.958 with a high category. The results of the test data are typically distributed and homogeneous. This is evidenced by the paired sample test with a significance value of 0.000 <0.05. The data on the use of e-learning was obtained through learning observations which included e-learning systems, e-learning content, and e-learning infrastructure. E-learning system uses learning media such as zoom application, WhatsApp, and google classroom. E-learning content in the form of teaching videos and electronic math books in the format of applications that can be downloaded through the Playstore. E-learning infrastructure is used in learning activities, such as computers, laptops, and mobile phones connected to the network. The research was carried out as a whole and simultaneously. The value of learning motivation before e-learning was 48.033, an increase of 14.87 after the use of e-learning, with a total value of learning motivation of 62.9.